An integrated in silico and in vivo approach to determine the effects of three commonly used surfactants sodium dodecyl sulphate, cetylpyridinium chloride and sodium laureth sulphate on growth rate and hematology in Cyprinus carpio L. (12th February 2022) - Bhattacharya, Ritwick; Daoud, Ismail; Chatterjee, Arnab; Chatterjee, Soumendranath; Saha, Nimai Chandra
Abstract: The purpose of this work is to evaluate the homology modeling, in silico prediction, and characterization of somatotropin and erythropoietin from Cyprinus carpio as well as molecular docking and simulation experiments between the modeled proteins and surfactants sodium dodecyl sulfate (SDS), sodium laureth sulfate (SLES) and cetylpyridinium chloride (CPC). Using the best fit template structure, homology modeling of somatotropin and erythropoietin of Cyprinus carpio respectively was conducted. The model structures were improved further with 3Drefine, and the final 3D structures were verified with PROCHEK, ERRATA and ProQ. The physiochemical, as well as the stereochemical parameters of the modeled proteins, were evaluated using ExPASy's ProtParam. Molecular docking calculations, protein-ligand interactions, and protein flexibility analysis were carried out to determine the binding pattern of each ligand to the targeted proteins and their effect on the overall proteins' conformation. Our in silico analysis showed that hydrophobic interactions with the active site amino acid residues of the modeled proteins (somatotropin and erythropoietin) were more prevalent than hydrogen bonds and salt bridges that affect the flexibility and stability of the somatotropin and erythropoietin as revealed from our protein flexibility analysis. The in vivo analysis showed that sublethal concentrations of SDS, SLES, and CPC negatively affected the growth and hematological parameters of Cyprinus carpio . Hence, it may be inferred from the study that the alterations in the flexibility of somatotropin and erythropoietin of Cyprinus carpio upon addition of SDS, CPC and SLES might be attributable to the reduction in growth and hematological parameters.